Analisis Kombinasi Vertical Projection Profile (VPP) Dan Top Down Profile (TDP) Dalam Segmentasi Karakter Pada Aplikasi OCR - Amelia Pratiwi; Yuyun Dwi Lestari; Yessy Fitri Annisah Lubis (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Segmentation digital images is a process to separate an object from the background or background, so that the object can be processed for other purposes. Along with the development of technology in applications that process digital images, the segmentation process is becoming increasingly necessary. vpp and tdp are image segmentation processing that uses a mapping of images that are different from digital image data and performsa segmentation process on the frequency of the pixel data found. This process provides its own convenience for the segmentation process because the reading process is light and also facilitates the system with a simple process